Effect of vitamin E and zinc supplementation in pre and post partum period in crossbred cows on anti-oxidant, immunity status and performance of new born calves : Pre and post partum period vitamin E and zinc supplementation effect on performance of new born calves - Sambyal, Madhu Suman; Phondba, Bhupendra T.; Thakur, Devesh; Kaur, Harjit (Indian Journal of Dairy Science, 2023)
The present study was undertaken to study the effect of zinc supplementation alone and its combination with vitamin E on growth, anti oxidant status and immunity status of new born calves of crossbred cows. The cows were supplemented with 0 (T0), Zn @ 80 ppm (T1) and Zn @ 80 ppm + 1000 IU α-tocopheryl acetate/d (T2) from 60 days prepartum up to 90 days postpartum. The fat, SNF, total solid, protein, Zn and Cu contents content of colostrum showing no effect of dietary treatments but α-tocopherol content was higher significantly (P<0.01) in group T2 as compared to other groups. Total immunoglobulin in colostrum of T2 group is 25.87% higher than control. There was no effect of dietary treatments on plasma Zn and Cu levels of calves, however α-tocopherol concentration at day 5 was significantly (P<0.05) higher in group T2 as compared to other groups. Status of antioxidant enzymes, lymphocyte proliferation index, total and differential leukocyte count was not affected by the treatments. Higher birth weight (P<0.05) has been obtained in group T2 group as compared to other group. Calves from treatment groups showed lower incidence of morbidity and mortality due to calf scour and other infectious diseases compared to control.